Competing with multinational enterprises' entry: Search strategy, environmental complexity, and survival of local firms. Issue 4 (August 2019) - Wu, Jie; Lao, Ka Fai; Wan, Feng; Li, Jiatao
Highlights: Competitive dynamics between multinational enterprises (MNEs)'s entry and local firms is examined. The combination of the agent-based simulation model and the economic model of competition is applied. MNEs' entry firstly reduces the survival rate of local firms, and this effect is heightened by environment complexity, but diminishes over time. Local firms with a broader knowledge search are better able to confront the negative impact of MNEs' entry over time. The negative effect of MNEs' entry is weaker for local firms with a strong retrieval capacity. Abstract: This study examines the competitive dynamics between foreign and local firms. We posit that multinational enterprises (MNEs)'s entry in foreign markets significantly reduces the survival rate of local firms in the short term, but that this effect gradually diminishes over time. The proposed conceptual framework is operationalized through the combination of the widely used agent-based model and the economic model of competition. The agent-based model allows us to study the behavior of firms under the context of different markets and the environmental complexity while the competition model determines the competition between firms as well as the entry and exit of firms. Our results obtained from the simulation study reveal that the negative effect of foreign entry is heightened as environmental complexity increases. However, local firms with a broader knowledge search are better able to confront the negative impact of foreign entry over time. We also find that the negative effect of foreign entry on the survival of local firms is weaker for local firms with a strong retrieval capacity.